Extracellular Vesicles Derived From Stem Cells in Intervertebral Disc Degeneration - Wu, Xinjie; Sun, Wei (Frontiers in Cell and Developmental Biology, 2022)
Intervertebral disc degeneration (IVDD) is the leading cause of low back pain related to degradation of cartilaginous tissues, mainly resulting from oxidative stress, cell apoptosis, and extracellular matrix degradation. Extracellular vesicles (EVs) exist in all bodily fluids and can be produced by all types of cells. Stem cell-derived EVs (SC-EVs), which are main paracrine components of stem cells, have gained significant attention in the field of regenerative medicine. Over the past years, accumulating evidence indicates the therapeutic and diagnostic potentials of EVs in IVDD. The main mechanisms involve induction of regenerative phenotypes, apoptosis alleviation, and immune modulation. In addition, the efficiency of SC-EVs can be enhanced by choosing appropriate donor cells and cell phenotypes, optimizing cell culture conditions or engineering EVs to delivery drugs and targeting molecules. Given the importance and novelty of SC-EVs, we give an overview of SC-EVs and discuss the roles of SC-EVs in IVDD.